2016
DOI: 10.1111/jav.00786
|View full text |Cite
|
Sign up to set email alerts
|

Egg rejection and clutch phenotype variation in the plain priniaPrinia inornata

Abstract: Avian hosts of brood parasites can evolve anti‐parasitic defenses to recognize and reject foreign eggs from their nests. Theory predicts that higher inter‐clutch and lower intra‐clutch variation in egg appearance facilitates hosts to detect parasitic eggs as egg‐rejection mainly depends on the appearance of the egg. Therefore, we predict that egg patterns and rejection rates will differ when hosts face different intensity of cuckoo parasitism. We tested this prediction in two populations of the plain prinia Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Clutch size of the Yellow-bellied Prinia is usually five, incubation period lasts for 11-14 days, and their brood period lasts for 11-12 days. The chickens of the Yellow-bellied Prinia are altricial (Ding et al 2007(Ding et al , 2016(Ding et al , 2017Yang et al 2013Yang et al , 2014Wang et al 2016).…”
Section: Study Speciesmentioning
confidence: 99%
“…Clutch size of the Yellow-bellied Prinia is usually five, incubation period lasts for 11-14 days, and their brood period lasts for 11-12 days. The chickens of the Yellow-bellied Prinia are altricial (Ding et al 2007(Ding et al , 2016(Ding et al , 2017Yang et al 2013Yang et al , 2014Wang et al 2016).…”
Section: Study Speciesmentioning
confidence: 99%
“…Both island and mainland populations of plain prinias are grasp-type egg rejecters. However, the island population rejected only 4.76% of all white model eggs, compared to the 63.64% rejected by the mainland population [11]. In this study, the eggs of yellow-bellied prinia (Prinia flaviventris) were used as parasitic eggs for both mainland and island populations of the plain prinia.…”
Section: Parasitic Eggsmentioning
confidence: 86%
“…A recent study showed that the rejection of nonmimetic model eggs by the Taiwanese plain prinia population was 4.8%, considerably lower than the rejection rate of the mainland population (63.6%) [11]. Based on these previous results using model eggs [11], we used various real eggs for our artificial parasitism experiments. Both island and mainland populations of plain prinias are grasp-type egg rejecters.…”
Section: Parasitic Eggsmentioning
confidence: 97%
See 1 more Smart Citation
“…Two Prinia species exist that are closely related to the rufescent prinia in South China: the plain prinia ( P. inornata ) and the gray‐breasted prinia ( P. hodgsonii ). The plain prinia lays white or blue eggs with reddish spots (Wang et al., ), seemingly a subset of the four egg types observed in the rufescent prinia. Egg phenotype of the gray‐breasted prinia is unknown.…”
Section: Discussionmentioning
confidence: 99%